METHODS OF CONTROLLING THE POSITION OF FLAT PARTS OF SHOE BY ASYMMETRY OF THE SURFACE PROPERTIES - КАРМАЛІТА, А. К.; ПУНДИК, С. І. (Technologies and Engineering, 2024)
Purpose. A systematic search for rational and effective solutions for the creation of devices for controlling the position and orientation of flat parts of shoes according to the asymmetry of the surfaces for the organization of the working environment of industrial robots. Methodology. The method of systematic, theoretical and comparative analyzes was used in the work. Theoretical studies are based on the basic principles of physics and technology of light industry production. Findings. It was established that the process of orienting robotic objects is one of the elements of environmental organization; the orientation task includes position control elements. Therefore, control of the position of robotics objects is an integral part of the organization of the environment. For the orientation of flat shoe parts, along with the control of the position of the parts according to geometric features, it is necessary to control their position according to the asymmetry of the surface properties. The devices for controlling the position of flat parts based on the asymmetry of the surface properties existing in instrument and mechanical engineering cannot be applied to most of the flat parts of shoes, since the properties of the surfaces of these parts have their own specificity. The previously investigated methods of controlling the position of shoe parts by the asymmetry of the surface properties are complicated and unreliable in operation, since they are all multi-stage systems in which the signal received from the control sensors, before giving a command to the actuator, must pass a long route through the comparing element, amplifier, executive element. Each of these stages is a complex device, and a malfunction of one of them leads to a malfunction of the entire system. Therefore, it is necessary to create new, more advanced and reliable methods of control, to conduct their research aimed at obtaining clear recommendations and typical methods of calculating control devices. Originality. A systematic analysis of the methods of controlling the position of flat parts according to the asymmetry of surfaces in various industries was carried out. The classification of methods of controlling the position of flat parts depending on their physical and mechanical properties was proposed. It has been established that the existing methods are ineffective for flat shoe parts and there is a need to create new, more advanced and reliable control methods. Practical value. The obtained research results can be used in the design of devices for controlling the position and orientation of flat parts of shoes during their automatic submission to technological processing.